Effects of Workload and Compensation on Employee Performance of SMEs in Cirebon City - Adhariyanti, Hidayatul Ilma; Susijawati, Noveria (JENIUS (Jurnal Ilmiah Manajemen Sumber Daya Manusia), 2026)
This research aims to examine how workload and compensation influence the performance of employees working in coffee shop–based culinary SMEs in Cirebon City. Employee performance is a critical factor for SME sustainability, especially in the post-pandemic era where business competition intensifies. This study fills a gap by focusing on coffee shop SMEs in Cirebon City, a context rarely examined in previous research. Workload includes responsibility, employee awareness of the work they face, concentration, interaction between employees, repetitive and non-repetitive work, while compensation includes salary, bonuses, facilities, health insurance, and leave. This study was executed quantitatively using a survey approach where data were collected via questionnaires administered to 110 employees of coffee shop culinary SMEs in Cirebon City. This study utilized multiple linear regression analysis to investigate the correlation among variables. Multiple linear regression analysis showed that workload has a significant positive effect on employee performance (β = 0.693, p < 0.001), while compensation does not have a significant effect (β = 0.088, p = 0.133). The adjusted R² value was 0.613, indicating that workload and compensation jointly explain 61.3% of the variance in employee performance. These findings emphasize the importance of effective workload management, while compensation is not a driving factor in improving performance.